Kepercayaan Diri Anak Usia Dini dalam Kegiatan Public Speaking - Nur Jami’ah (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
This research aims to examine young children's self-confidence in public speaking activities. Self-confidence is an important aspect of children's development that influences their ability to communicate effectively in public. This study uses a qualitative approach with observation and interview methods to collect data from a group of young children who are involved in public speaking activities in formal education environments. The research results show that young children's self-confidence in public speaking activities can be increased through positive environmental support, consistent practice, and providing constructive feedback. A supportive environment includes teachers and parents who provide encouragement and recognition for children's efforts. In addition, activities that are systematically designed to involve children in speaking in front of their friends can strengthen their self-confidence. Structured public speaking practice helps children develop verbal and non-verbal communication skills, and reduces any fear or anxiety they may feel when speaking in public. Positive and constructive feedback from teachers and friends also plays an important role in strengthening children's self-confidence.